The Peningkatan Nilai Tambah Onggok Singkong dan Dedak Padi Sebagai Substrat pada Produksi Asam Sitrat - Kirana Sanggrami Sasmitaloka; Maritsya Dita Kurnia Putri (LPPM Universitas Terbuka, 2023)
Worldwide demand for citric acid is increasing faster than production, so a more economical process is needed. Aspergillus niger is capable of producing citric acid from agroindustrial by-products. Utilization of cassava dregs and rice bran as substrates in citric acid fermentation can increase the added value of these agroindustrial by-products. This research aims to study the utilization of cassava dregs and rice bran as citric acid production substrates by Aspergillus niger on solid state fermentation and the characteristics of the citric acid they produce. The study was designed using a completely randomized design with treatment combinations between the percentage of inoculum volume w/v (x1: 2.5%; x2: 5%; and x3: 7.5%) and incubation time (y1: 1 day; y2: 2 days; y3: 3 days; y4: 4 days; y5: 5 days; y6: 6 days; and y7: 7 days), repeated four times. The addition of Aspergillus niger inoculum volume as much as 5% w/v with an incubation time of five days can produce optimal citric acid. In this combination of treatments, a pH value of 2.65, a total acid of 13.91 g/L, and a citric acid content of 9.74 g/L were produced.